SERUM ZINC LEVELS IN SUDANESE PATIENTS WITH ACUTE LYMPHOCYTIC LEUKEMIA - Mohamed, Omar W. A.; Bakhiet, Sahar M.; Gerges, Hani K. F.; Kordofani, Anwaar A.Y. (International Journal of Clinical and Biomedical Research, 2017)
Background: Zinc acts as growth protector for neoplastic cells and its deficiency was contributed to carcinogenesis. However, the determinations of serum zinc in acute lymphocytic leukemia (ALL) prediction and prognosis requires more investigations. Objective: To evaluate and compare serum zinc in ALL patients and healthy controls and to correlate the serum zinc levels with hematological prognostic markers. Materials and methods: The study was conducted in Khartoum state-Sudan during the period from December 2013 to September 2014, it involved a case group of ALL patients (N=100) matched for age and gender with a control group (N=100). Serum copper and zinc levels and full blood count were investigated. Results: The ALL patients showed lower levels of Zn 0.73 ± 0.18 mg/dl compared to controls 1.01 ± 0.25 mg/dl [P = 0.003]. The serum Zn levels were inversely correlated with total white cell (-0.804, P < 0.0001) and blast counts (-0.935, P < 0.0001). Conclusion: These findings ALL associated with lower serum zinc levels and higher serum copper levels. The determination of serum zinc and copper could be used as ALL prognostic markers. KEYWORDS: Acute lymphoblastic leukemia; Zinc; Carcinogenesis.